A construção de representações por meio da leitura extensiva aliada à sala de de aula orientada à ação na formação de professores leitores - Ciocari, Roberta Macedo (2018)
This work was about envisionment building in reading instruction through extensive reading and action-oriented classrooms. Data were collected in a group of students who were taking the subject called Extensive Reading in a Latto Sensu course – Languages and their Technologies – at the Institute of Federal Education (IFSul), in the campus of Passo Fundo. The 18 subjects of the research had their voices recorded during discussions in the classes. Two questionnaires were also applied to them – one before classes started, and the other, on the last meeting. Data analysis had as its first objective to verify how the subjects developed their understandings about the fiction they read. This analysis was based on the 5 stances of the envisionment building theorizations by Judith Langer (2005, 2011a, 2011b). The second objective was to discover the opinion of the subjects about the methodology which was used in the classes. The results indicated the effective envisionment building by the subjects through the 5 stances mentioned by the North-American scholar. They also showed a growth in the enthusiasm and in the motivation for reading and for the professional and personal development of the subjects. The study showed that a reading instruction approach that has as its basis the extensive reading and action-oriented activities, with the consequent envisionment building, is effective concerning reader education, and it also helps to increase the teachers’ pedagogical repertoire.